1977
DOI: 10.1159/000122721
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns in Growth Hormone Deficient Children and Age-Matched Controls: Developmental Considerations

Abstract: Ten patients with isolated growth hormone (GH) deficiency and 13 age-matched normal controls were studied. All patients were below the 3rd percentile in height and weight. All but 1 subject were studied for 3 or 4 consecutive nights in the sleep laboratory which included monitoring of the EEG, EOG, EMG, and EKG. GH samples were taken during sleep in 6 of the 10 patients. There were no significant differences in the slow-wave sleep (SWS) parameter between the 2 groups, nor was there any difference when all grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Our data confirm in part the first report on GHD children before GH therapy [17] that showed only an increase in sleep stage 1 compared to age-matched normative data (9.7 vs. 2.3%); unfortunately no other parameters of sleep fragmentation were reported in that study. Our results are in agreement with Van Cauter et al [16] who showed, in adults with GHD of pituitary origin, an increased sleep fragmentation (indicated by an increase in WASO and arousal index and by a decrease in sleep efficiency and sleep maintenance index), while no differences were evident in sleep stage distribution.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our data confirm in part the first report on GHD children before GH therapy [17] that showed only an increase in sleep stage 1 compared to age-matched normative data (9.7 vs. 2.3%); unfortunately no other parameters of sleep fragmentation were reported in that study. Our results are in agreement with Van Cauter et al [16] who showed, in adults with GHD of pituitary origin, an increased sleep fragmentation (indicated by an increase in WASO and arousal index and by a decrease in sleep efficiency and sleep maintenance index), while no differences were evident in sleep stage distribution.…”
Section: Discussionsupporting
confidence: 88%
“…The different studies on the effects of GH replacement in GHD patients showed that it minimally affects sleep architecture, night sleep and daytime sleep propensity [6,17,20,21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH is, in fact, capable of promoting REMS; increases in REMS are reported after acute administration of GH in rats (Drucker-Colin et al, 1975), cats (Stern et al, 1975), and humans (Mendelson et al, 1980), whereas immunoneutralization of GH is followed by decreases in REMS in rats (Obál et al, 1997). GH deficiency is often associated with decreases in REMS in children, but REMS might be normal in GH-deficient young adults (Orr et al, 1977;Hayashi et al, 1992). We suggest that the decreases in REMS result from the GH deficiency in the dw/dw rat, whereas the intracerebral hGH compensates for the loss of pituitary GH and maintains normal REMS in the TH-hGH transgenic mouse.…”
Section: Discussionmentioning
confidence: 78%
“…But, from reports of several other studies, such a SWS-hGH link has to be qualified. For example, SWS deprivation results in smaller, but still significant, amounts of hGH release during the remaining sleep (Karacan, Rosenbloom, Will iams, Finley, & Hursch, 1971;Sassin, Parker, Johnson, Rossman, Mace, & Gotlin, 1969); hGH-inhibiting factor (somatostatin) or an elevation in plasma-free fatty acids will suppress the sleep hGH release but not SWS (Lipman, Taylor, Schenk, & Mintz, 1972;Lucke, Hoffken, & von zur Muhlen, 1976); sleep hGH can be elevated without there being any significant quantitative effect upon SWS (Adamson, Hunter, Ogunremi, Oswald, & Percy-Robb, 1974); finally, hGH-deficient children have normal SWS levels but no sleep-hGH release (Orr, Vogel, Stahl, Griffiths, & Seely, 1977).…”
mentioning
confidence: 99%